Digital democracy: A systematic literature review - Congge, Umar; Guillamón, María-Dolores; Nurmandi, Achmad; Salahudin; Sihidi, Iradhad Taqwa (Frontiers in Political Science, 2023)
Digital democracy provides a new space for community involvement in democratic life. This study aims to conduct a systematic literature review to uncover the trend of concepts in the study of digital democracy. This study used descriptive analysis with data sources derived from the Scopus database from the period between 2014 and 2020 (a total of 230 articles) and processed with VOSviewer. The results showed three dominant concepts, namely democracy, the internet, and movement. In addition, it was found that the digital era provides positive and negative impacts on democracy, that public knowledge in a quality digital democracy is important, and that there is strong elite control in virtual democracy. The results of this research can be used as a basis for developing digital democracy studies. Meanwhile, this study was limited by the fact that the articles reviewed were only sourced from Scopus and did not include publications from 2022. Therefore, future studies need to take a comparative analysis approach that uses the Web of Science (WoS) database and increases the time period in which articles are sourced.